Changes in Intra Ocular Pressure after Cataract Surgery - Rajni Sethia; Nirathya Anisha Pothuri; Aditya Desai; R.N. Kothari; Aarushi Shah; Jeet Patel (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Rise in Intraocular Pressure (IOP) is the major contributing factor to the pathology of glaucoma.Along with cataract, it is one of the leading causes of preventable blindness all over the world. Cataract surgerycan help reduce the IOP and our study helps confirm the same.Methods: Our study included 150 eyes of 150 patients undergoing cataract surgery by phacoemulsification bya single surgeon. Complete ocular examination was performed on all the patients which included uncorrected distancevisual acuity (UCVA) and best corrected visual acuity (BCVA) by Snellen’s chart, anterior segment by slit-lamp,IOP by Goldmann’s Applanation Tonometry (AT), gonioscopy by 4 mirror gonioscope, Anterior Chamber Depth(ACD) and Axial Length (AL) by A-scan. IOP measurements were taken between 9am and 10am.Conclusion: Our study divided the patients into 3 groups based on IOP i.e., <15, 15-19, and 19-23 mmHg of IOP.All the 3 groups showed a lesser IOP post cataract surgery. There was a significant decrease in IOP whenbaseline was compared with post op week 1, week 4 and week 12. Therefore our study confirms that cataract surgerywith PCIOL causes reduction in IOP which remains sustained for months.